(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
The article discusses the rules and techniques for organizing volleyball clubs in higher education institutions, the importance of volleyball in the system of physical education and sports, the equipment of the training area, its simplicity, spectacularness and excitement, beauty, and the diversity of game tactics and its methodology.